STRUKTUR, MAKNA, DAN FUNGSI MANTRA PENGOBATAN MASYARAKAT MELAYU SEMITAU KABUPATEN KAPUAS HULU - Imam Agus Faisal (Balai Bahasa Kalimantan Barat, 2018)
This Research was conducted since a concept about the importance of immersing the verbal literature. According to the observation conducted by the researcher, a research about the verbal literature of locals of Semitau Malay from Kapuas Hulu Regency has not been conducted by students of Tanjungpura university. The objective of this research was to describe and interpret the structure, the meaning, and the function contained in healing spells of locals of Semitau Malay from Kapuas Hulu Regency, including the implementation in a process of teaching and learning at school. The method of this reseach was a descriptive and hermeneutical research in a descriptive form. The approach in this research was structural for analyzing the structure of spells, such as: word and rhyme choices, including the hermeneutical approach to analyze the meaning and the function of the spells. Based on the result of analysis, word choices were general words and particular words. The rhymes were full rhyme, absolute rhyme, half rhyme, alliterative rhyme, assonance rhyme, integrated rhyme, initial rhyme, center rhyme, final rhyme, horizontal rhyme, vertical rhyme, straight rhyme, crossed rhyme, and free rhyme. The meaning of spells was about divinity, society, and personality. The function of spells was a projection, a verifier of culture regulation, and an education tool.